Clinical Value of NT-proBNP and Performance Myocardial Index as an Echocardiographic Predictor of Early Cardiac Involvement in Patients with Carcinoid Syndrome - Nitu, Ileana; Baciu, Ionela; Galoiu, Simona; Capatana, Cristina; Burcea, Iulia Florentina; Greere, Daniela; Poiana, Catalina (Archives of Clinical and Biomedical Research, 2022)
Introduction: Carcinoid heart disease is a rare cause of right-sided valvular dysfunction, primarily mediated by serotonin. It is an important complication in patients with carcinoid syndrome which represents a major cause of morbidity and mortality. Objectives: We aim to present our own experience regarding early myocardial dysfunction in patients with carcinoid syndrome by using predictive two-dimensional echocardiographic parameters and cardiac biomarkers. Methods: 40 patients (35-90 year old, 62% female and 38% male patients; 20 non-hypertensive patients and 20 patients with arterial hypertension) with carcinoid syndrome and 20 healthy sex and age-matched subjects were consequently enrolled between October 2017 and June 2021. All patients underwent comprehensive two-dimensional echocardiography with additional tissue Doppler and speckle-tracking techniques. The Myocardial Performance Index (MPI) of both ventricles was calculated as (isovolumic contraction time “ICT”+ relaxation time “IRT”)/Ejection time “ET”. Besides, cardiac biomarkers (plasma level of pro-brain natriuretic peptide- NT-proBNP) were measured for each patient. Results: Patients with carcinoid syndrome and arterial hypertension present higher values of MPI in comparison to non-hypertensive patients; moreover, all of the patients with carcinoid tumour tend to develop early myocardial dysfunction and higher MPI values than healthy subjects. This might be of particularly clinical interest in carcinoid syndrome with aggressive outcome. Discussion: in the present study, higher values of MPI of both left and right ventricles, as well as plasma level of NT-proBNP proved to be of extremely importance in order to